2022
DOI: 10.1007/s40145-021-0527-5
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity and bending strength of SiC composites reinforced by pitch-based carbon fibers

Abstract: In this work, pitch-based carbon fibers were utilized to reinforce silicon carbide (SiC) composites via reaction melting infiltration (RMI) method by controlling the reaction temperature and resin carbon content. Thermal conductivities and bending strengths of composites obtained under different preparation conditions were characterized by various analytical methods. Results showed the formation of SiC whiskers (SiCw) during RMI process according to vapor—solid (VS) mechanism. SiCw played an important role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 51 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…Besides, the introduction of the second phase into the ceramics can significantly improve the mechanical properties of the ceramic matrix composites. [12][13][14][15][16][17] With high strength, hardness, elastic modulus, excellent aspect ratio, and good chemical stability, SiC whiskers (SiCw) are used as significant toughening materials for metal and ceramic matrix composites. For instance, Song et al 18 coated a layer of phenolic resin on the surface of SiCw to strengthen SiC ceramics; they found that the fracture toughness and strength of SiC-15 wt% SiCw composites were increased by 45% (from 200 to 290 MPa) and 75% (from 3.2 to 5.6 MPa⋅m 1/2 ), respectively, compared to the pure SiC ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the introduction of the second phase into the ceramics can significantly improve the mechanical properties of the ceramic matrix composites. [12][13][14][15][16][17] With high strength, hardness, elastic modulus, excellent aspect ratio, and good chemical stability, SiC whiskers (SiCw) are used as significant toughening materials for metal and ceramic matrix composites. For instance, Song et al 18 coated a layer of phenolic resin on the surface of SiCw to strengthen SiC ceramics; they found that the fracture toughness and strength of SiC-15 wt% SiCw composites were increased by 45% (from 200 to 290 MPa) and 75% (from 3.2 to 5.6 MPa⋅m 1/2 ), respectively, compared to the pure SiC ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…To improve fracture properties of the UHTCs, short and long carbon or silicon carbide fibres have been added [8][9][10][11][12][13][14][15]. These composites are called ultra-hightemperature ceramic matrix composites (UHTCMCs).…”
Section: Introduction mentioning
confidence: 99%
“…Fig 13. Morphologies of graded sample (L2) composed of alternation 20% C f -reinforced layers (A) and 0% C f layers (B).…”
mentioning
confidence: 99%
“…Silicon carbide fiber reinforced silicon carbide ceramic matrix composites (SiC f /SiC CMCs) are promising candidates for application as hot section components in future aeroengines due to their inherently low weight, high-temperature capabilities, and tolerance of damage. [1][2][3][4] Environmental barrier coatings (EBCs) are increasingly important, and they are being developed to protect hotsection components from degradation in high-temperature water vapor and molten silicate deposits environments. 5,6 Advanced coating design concepts are currently explored and tested, including multilayered and integrated thermal and EBCs (TEBCs).…”
Section: Introductionmentioning
confidence: 99%
“…The apparent densities of δ-Yb 4 Hf 3 O 12 and δ-Lu 4 Hf 3 O 12 are measured as 9.73 and 9.88 g/cm3 , respectively. Samples were obtained with relative densities higher than 97%.…”
mentioning
confidence: 97%